Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

[tex]y^2+3y+2=0[/tex]

Sagot :

Answer:

y = - 2, y = - 1

Step-by-step explanation:

y² + 3y + 2 = 0

Consider the factors of the constant term (+ 2) which sum to give the coefficient of the y- term (+ 3)

The factors are + 2 and + 1 , since

2 × 1 = 2 and 2 + 1 = 3 , then

(y + 2)(y + 1) = 0

Equate each factor to zero and solve for y

y + 2 = 0 ⇒ y = - 2

y + 1 = 0 ⇒ y = - 1